Urbanization, urban concentration and economic growth in developing countries - Luisito Bertinelli; Eric Strobl (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2003)
We investigate how urban concentration and urbanization affect economic growth in developing countries. Using semi-parametric estimation techniques on a cross-country panel of 39 countries for the years 1960-1990 we discover a U-shaped relationship for urban concentration. This suggests the existence of an 'urban-concentration trap' where marginal increases in urban concentration would reduce growth for about a third of our sample. Furthermore, there appears to be no systematic relationship between urbanization and economic growth.
Keywords: 330; urban concentration; economic development; LDCs; semiparametric estimations